The leadership challenge how to make extraordinary things happen in organizations - Kouzes, James M. (San Francisco Jossey-Bass, 2012)
For more than 25 years, The Leadership Challenge has been the most trusted source on becoming a better leader, selling more than 2 million copies in over 20 languages since its first publication. Based on Kouzes and Posner's extensive research, this all-new edition casts their enduring work in context for today's world, proving how leadership is a relationship that must be nurtured, and most importantly, that it can be learned.
Includes bibliographical references Index
Keywords: Leadership